SIMRS Analysis using SUS and PIECES for User Satisfaction (Case Study: XYZ Hospital) - Nyoman Alvia Wirayani; I Made Agus Dwi Suarjaya; Putu Wira Buana (Journal of Computer Science and Informatics Engineering (J-Cosine), 2023)
Management Information System of a Hospital is an information technology system that manages the entire service process flow within the hospital environment to obtain accurate information. One way to optimize and improve the performance of the SIMRS is by assessing user satisfaction from the perspective of employees at XYZ Hospital, requiring an evaluation. The methods used in the satisfaction analysis testing are System Usability Scale (SUS) and PIECES. The purpose of this study is to determine the level of employee satisfaction and identify the service aspects in SIMRS that need to be improved and maintained, as well as the creation of a service chatbot for distributing user satisfaction questionnaires and assisting in providing solutions to employees to resolve frequently asked problems. The System Usability Scale method obtained a score of 57.15 in the Okay category and grade D, while the PIECES method received a rating of 3.57 in the Satisfied category and grade B.